Financial Evaluation of Kidney Transplant With Hepatitis C Viremic Donors to Uninfected Recipients - David A. Axelrod, MD, MBA; Krista L. Lentine, MD, PhD; Ramji Balakrishnan, PhD; Su-Hsin Chang, PhD; Terek Alhamad, MD; Huiling Xiao, MS; Bertran L. Kasiske, MD; Roy D. Bloom, MD; Mark A. Schnitzler, PhD (Transplantation Direct, 2020)
Background. Kidney transplantation with hepatitis C viremic (dHCV+) donors appears safe for recipients without HCV when accompanied by direct acting antiviral (DAA) treatment. However, US programs have been reluctant to embrace this approach due to concern about insurance coverage. While the cost of DAA treatment is currently offset by the reduction in waiting time, increased competition for dHCV+ organs may reduce this advantage. This analysis sought to demonstrate the financial benefit of dHCV+ transplant for third-party health insurers to expand coverage availability. Methods. An economic analysis was developed using a Markov model for 2 decisions: first, to accept a dHCV+ organ versus wait for a dHCV uninfected organ; or second, accept a high kidney donor profile index (KDPI) (>85) organ versus wait for a better quality dHCV+ organ. The analysis used Medicare payments, historical survival data, cost report data, and an estimated cost of DAA of $29 874. Results. In the first analysis, using dHCV+ kidneys reduced the cost of end-stage kidney disease care if the wait for a dHCV uninfected organ exceeded 11.5 months. The financial breakeven point differed according to the cost of DAA treatment. In the second analysis, declining a high-KDPI organ in favor of a waiting dHCV+ organ was marginally clinically beneficial if waiting times were <12 months but not cost effective. Conclusions. dHCV+ transplant appears to be economically and clinically advantageous compared with waiting for dHCV-uninfected transplant but should not replace high-KDPI transplant when appropriate. Despite the high cost of DAA therapy, health insurers benefit financially from dHCV+ transplant within 1 year.